What substances do we inhale? - Air quality measurement using an Android-based application - Endang Surahman; Eko Sujarwanto; Irwan Muhammad Ridwan (Universitas Riau, 2024)
Measurement of pollutants in the air is important because it’s related to health issues and environmental sustainability. This study aims to measure the concentration of pollutants in the air and learn in the environmental physics course. Measurements were carried out in 108 places with various characters in West Java Province i.e. factories, public facilities, highways, and residential. Measurements were made using the BreezoMeter application to measure the concentration of O3, CO, SO2, NO2, PM2.5, and PM10. In general, the results show that air quality is in a good category based on the air pollutant standard index. Although the air quality is in a good category in general, some places have the air quality in the unhealthy category. By knowing air quality, it is hoped that people will be more concerned about environmental sustainability and health.